Educating the Public About Police Through Public Service Announcements in Lima, Ohio, 1995-1997 - Chamlin, Mitchell B. ([Verlag nicht ermittelbar], 2000)
This study was designed to analyze the impact of four televised public service announcements (PSAs) aired for three months in Lima, Ohio. The researchers sought to answer three specific research questions: (1) Were the PSAs effective in transferring knowledge to citizens about the police? (2) Did the PSAs have an impact on resident satisfaction with the police? and (3) Did the PSAs have an impact on the behavior of citizens interacting with the police? To assess public attitudes about the Lima police and to determine whether the substance of the PSAs was being communicated to the residents of Lima, three waves of telephone interviews were conducted (Part 1). The first telephone interviews were conducted in April 1996 with approximately 500 randomly selected Lima residents. These were baseline interviews that took place before the PSAs aired. The survey instrument used in the first interview assessed resident satisfaction with the police and the services they provided. After completion of the Wave 1 interviews, the PSAs were aired on television for three months (June 5-August 28, 1996). After August 28, the PSAs were removed from general circulation. A second wave of telephone interviews was conducted in September 1996 with a different group of randomly selected Lima residents. The same survey instrument used during the first interviews was administered during the second wave, with additional questions added relating to whether the respondent saw any of the PSAs. A third group of randomly selected Lima residents was contacted via the telephone in January 1997 for the final wave of interviews. The final interviews utilized the identical survey instrument used during Wave 2. The focus of this follow-up survey was on citizen retention, over time, of the information communicated in the PSAs. Official data collected from computerized records maintained by the Lima Police Department were also collected to monitor changes in citizen behavior (Part 2). The records data span 127 weeks, from January 1, 1995, to June 7, 1997, which includes 74 weeks of pre-PSA data and 53 weeks of data for the period during the initial airing of the first PSA and thereafter. Variables in Part 1 include whether respondents were interested in learning about what to do if stopped by the police, what actions they had displayed when stopped by the police, if they would defend another person being treated unfairly by the police, how responsible they felt (as a citizen) in preventing crimes, the likelihood of calling the police if they were aware of a crime, perception of crime and fear of crime, and whether there had been an increase or decrease in the level of crime in their neighborhoods. Respondents were also asked about the amount of television they watched, whether they saw any of the public service announcements and if so to rate them, whether the PSAs provided information not already known, whether any of the PSA topics had come up in conversations with family or friends, and whether the respondent would like to see more PSAs in the future. Finally, respondents were asked whether the police were doing as much as they could to make the neighborhood safe, how responsive the police were to nonemergency matters, and to rate their overall satisfaction with the Lima Police Department and its various services. Demographic variables for Part 1 include the race, gender, age, marital status, level of education, employment status, and income level of each respondent. Variables in Part 2 cover police use-of-force or resisting arrest incidents that took place during the study period, whether the PSA aired during the week in which a use-of-force or resisting arrest incident took place, the number of supplemental police use-of-force reports that were made, and the number of resisting arrest charges made.